Regulation of electron transfer processes affects phototrophic mat structure and activity - Ha, Phuc T.; Renslow, Ryan S.; Atci, Erhan; Reardon, Patrick N.; Lindemann, Stephen R.; Fredrickson, James K.; Call, Douglas R.; Beyenal, Haluk (Frontiers in Microbiology, 2015)
Phototrophic microbial mats are among the most diverse ecosystems in nature. These systems undergo daily cycles in redox potential caused by variations in light energy input and metabolic interactions among the microbial species. In this work, solid electrodes with controlled potentials were placed under mats to study the electron transfer processes between the electrode and the microbial mat. The phototrophic microbial mat was harvested from Hot Lake, a hypersaline, epsomitic lake located near Oroville (Washington, USA). We operated two reactors: graphite electrodes were polarized at potentials of -700 mVAg/AgCl [cathodic (CAT) mat system] and +300 mVAg/AgCl [anodic (AN) mat system] and the electron transfer rates between the electrode and mat were monitored. We observed a diel cycle of electron transfer rates for both AN and CAT mat systems. Interestingly, the CAT mats generated the highest reducing current at the same time points that the AN mats showed the highest oxidizing current. To characterize the physicochemical factors influencing electron transfer processes, we measured depth profiles of dissolved oxygen (DO) and sulfide in the mats using microelectrodes. We further demonstrated that the mat-to-electrode and electrode-to-mat electron transfer rates were light- and temperature-dependent. Using nuclear magnetic resonance (NMR) imaging, we determined that the electrode potential regulated the diffusivity and porosity of the microbial mats. Both porosity and diffusivity were higher in the CAT mats than in the AN mats. We also used NMR spectroscopy for high-resolution quantitative metabolite analysis and found that the CAT mats had significantly higher concentrations of osmoprotectants such as betaine and trehalose. Subsequently, we performed amplicon sequencing across the V4 region of the 16S rRNA gene of incubated mats to understand the impact of electrode potential on microbial community structure. These data suggested that variation in the electrochemical conditions under which mats were generated significantly impacted the relative abundances of mat members and mat metabolism.